Ogba Language: An Exploration of Code-Switching and Code-Mixing in Ogba Speakers’ Linguistic Behavior - Stanley Ordu; Better Odukwu (Journal of Language and Linguistics in Society, 2024)
This paper investigates the phenomenon of code-switching and code-mixing among the Ogba people in Rivers State, Nigeria, who speak the Ogba language. The study examines Ogba speakers’ linguistic behavior in multilingual settings, as well as the sociolinguistic factors that influence their language choices. The study utilized quantitative methods, and Myers-Scotton’s (1993) Matrix Language Frame (MLF) model guided this work. The results show that the study of code-switching and code-mixing among Ogba speakers provides valuable insights into the dynamic nature of language use and identity construction. In conclusion, the work provides a comprehensive analysis of how and why speakers switch and mix codes, as well as the implications of these practices for the Ogba language and identity.